THEME: ASSESSMENT AND EVALUATION IN INTENSIVE LANGUAGE TEACHING - Safarova Dildora; Sangirova Marjona (Ustozlar uchun, 2025)
This article explores the significance of assessment and evaluation in intensive language teaching, highlighting various methods used to measure student progress and enhance instructional effectiveness. It discusses formative, summative, diagnostic, and performance-based assessments, emphasizing their role in providing continuous feedback and improving language proficiency. The integration of technology in assessment, including digital tools and artificial intelligence, is examined for its impact on real-time progress tracking. Additionally, the article addresses challenges such as test anxiety, cultural differences, and the reliability of evaluation methods. A balanced approach to assessment ensures a comprehensive understanding of student achievements and fosters a more effective language learning experience.